The fall of Gondolin - Tolkien, J. R. R. 1892-1973 (HarperCollinsPublishers, 2018)
In the Tale of The Fall of Gondolin are two of the greatest powers in the world. There is Morgoth of the uttermost evil, unseen in this story but ruling over a vast military power from his fortress of Angband. Deeply opposed to Morgoth is Ulmo, second in might only to Manwë, chief of the Valar. Central to this enmity of the gods is the city of Gondolin, beautiful but undiscoverable. It was built and peopled by Noldorin Elves who, when they dwelt in Valinor, the land of the gods, rebelled against their rule and fled to Middle-earth. Turgon King of Gondolin is hated and feared above all his enemies by Morgoth, who seeks in vain to discover the marvellously hidden city, while the gods in Valinor in heated debate largely refuse to intervene in support of Ulmo's desires and designs
Keywords: Middle Earth (Imaginary place) / Fiction; Fantasy fiction; Fiktionale Darstellung